Фінансові відносини як об’єкт посягання у злочинах кредитно-фінансової системи - Бобошко, О. М.; Нестеренко, К. О.; Boboshko, Olena; Nesterenko, Kateryna (Одеса : Гельветика, 2019)
У роботі надано комплексну характеристику фінансових відносин як об’єкту посягання злочину у кредитно-фінансовій системі. Здійснено не лише аналіз досліджуваного явища, а й означено стан та тенденції злочинності у кредитно-фінансовій сфері. Досліджено причини та умови, що породжують кредитно-фінансову злочинність. Особливої уваги приділено вивченню фінансовим відносинам як об’єкту посягання у злочинах проти кредитно-фінансової системи. На підставі аналізу національного та міжнародного законодавства було не лише окреслено проблематику, а і розроблено пропозиції щодо вдосконалення діючого законодавства України. At present in Ukraine the credit and financial system is one of the main links in the sphere of finance, serving as the most determinant segment of the market economy and affects all the processes taking place in the society and the state. A special feature of the economic situation in Ukraine is that a significant part of the financial and legal institutions is practically can’t fully function without the proper, legal, in particular criminal legal support and protection. In this case, it’s not just about protecting budgetary interests of society, but also about the interests of individual depositors and shareholders, the protection of the interests of financial institutions from dubious managers and founders, from unlawful interference in their activity of law enforcement bodies, from persons who receive large credits by fraudulent or other illegal actions, not wanting their refund (including the price of its own bankruptcy), from organized crime groups, etc. A comprehensive description of financial relations as an object of an offense in the credit and financial system is provided in the paper. Not only the phenomenon under study, but also the state and trends of crime in the credit and financial sphere are analyzed. The reasons and conditions that give rise to credit and financial crime are investigated. Particular attention is paid to the study of financial relations as an object of encroachment in crimes against the credit and financial system. On the basis of the analysis of national and international legislation, the issues were outlined, but also proposals were made to improve the current legislation of Ukraine.
Бобошко О. М., Нестеренко К. О. Фінансові відносини як об’єкт посягання у злочинах кредитно-фінансової системи / О. М. Бобошк, К. О. Нестеренко // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 2. – C. 94 - 105
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; кримінальна відповідальність; фінансові злочини; кредитно-фінансова система; об’єкт злочину; кримінологія; уголовная ответственность; уголовная ответственность; кредитно-финансовая система; объект преступления; криминология; criminal liability; financial crime; credit and financial system; criminolog; financial relation